2017
DOI: 10.1007/s10802-016-0258-1
|View full text |Cite
|
Sign up to set email alerts
|

Mother-Child Interactions and Externalizing Behavior Problems in Preschoolers over Time: Inhibitory Control as a Mediator

Abstract: Previous research has shown links between parenting and externalizing behavior problems in young children over time. Associations between inhibitory control, one of the executive functions, and externalizing behavior problems are widely established as well. Yet, the role of inhibitory control in the maintenance and change of externalizing behavior problems over time remains unclear. We examined whether inhibitory control could explain the link between mother-child interactions measured on a moment-to-moment ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 76 publications
3
9
0
Order By: Relevance
“…The significant findings on the association between maternal noncollaborative communication acts and poorer IC provided confirming evidence for the deleterious effect of negative parenting on early executive function development (e.g., Hughes & Devine, 2019). Such pattern is also consistent with the recent finding that affective instability in mother-child interaction characterized by high maternal negative affect is associated with decreased IC in children over time (van Dijk et al, 2017). The significance of maternal noncollaborative speech to child IC may be explained by the negativity bias theory in social-emotional development, which argues that young children tend to use and learn from negative information far more than positive information (Vaish, Grossmann, & Woodward, 2008).…”
Section: Relationship Between Maternal Verbal Communication and Chisupporting
confidence: 85%
“…The significant findings on the association between maternal noncollaborative communication acts and poorer IC provided confirming evidence for the deleterious effect of negative parenting on early executive function development (e.g., Hughes & Devine, 2019). Such pattern is also consistent with the recent finding that affective instability in mother-child interaction characterized by high maternal negative affect is associated with decreased IC in children over time (van Dijk et al, 2017). The significance of maternal noncollaborative speech to child IC may be explained by the negativity bias theory in social-emotional development, which argues that young children tend to use and learn from negative information far more than positive information (Vaish, Grossmann, & Woodward, 2008).…”
Section: Relationship Between Maternal Verbal Communication and Chisupporting
confidence: 85%
“…Some previous studies have suggested that maternal and paternal parenting styles play a central role in understanding the development of externalizing and internalizing behaviors [23,24], since parenting style exacerbates or reduces children’s behavioral problems [25,26,27]. The effects on development of parenting behaviors in childhood tend to be stable over time [28,29]. Depending on the parenting style they adopt, parents elect to use different discipline strategies to manage their children’s behavior and such strategies are considered a fundamental aspect of parenting [30].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review on the development of emotion regulation ( Eisenberg et al, 2010 ) reveals that children make great advances in their ability to exert control over their emotions in the preschool years while it improves more slowly into adulthood. Importantly, while individual differences in emotion regulatory skills are rather stable, they can serve as a mediator between parenting and children’s problem behaviors ( Belsky et al, 2007 ; Van Dijk et al, 2017 ). Moreover, interventions targeted at promoting self-regulation or regulating emotions result in more socially competent students ( Domitrovich et al, 2007 ; Low et al, 2015 ).…”
Section: Towards a Developmental Model Of Social Competencementioning
confidence: 99%